Sustainable Aquaculture Products: Implications of Consumer Awareness and of Consumer Preferences for Promising Market Communication in Germany. Issue 1 (2nd January 2018) - Zander, Katrin; Risius, Antje; Feucht, Yvonne; Janssen, Meike; Hamm, Ulrich
ABSTRACT: Sustainability issues are becoming increasingly important in Western food consumption. This research aims at identifying ways to increase the market share of sustainable fish from aquaculture by analyzing consumer awareness and preferences for sustainable aquaculture products and by drawing conclusions on improving communication in the German market. An integrative research approach was used: it began with an inventory of sustainable seafood products on the German market, followed by qualitative and quantitative consumer research, and ending with a stakeholder workshop, which reflected on the research outcome with practitioners. Sustainability and country of origin proved to be of minor relevance to the vast majority of the consumers interviewed. Indeed, attributes such as freshness, taste, and price frequently ranked higher. Like most of the other consumers, the small consumer segment that is generally interested in sustainability issues of food also often lacks knowledge of fish farming and its products. Consequently, communication of sustainability in aquaculture is challenging, and the development of this market requires concerted actions along the whole value chain, with the retail sector as the main actor.